Devir-cuidado: uma experimentação em saúde coletiva - Lira, Antonia Pautylla Silva (2016)
The private medicine transit to social medicine had its beginning in the late eighteenth century, extending during the nineteenth century. In this context, medical practice becomes a strategy of disciplinary societies in order to strengthen the development of the capitalist economy, not measuring efforts for the expansion of market relations, improvements in quality of life and state of growth. Therefore, social medicine, by the power of your new address, establish a number of measures which will enable more and more refined exercise of power over life. In the Brazilian context, social medicine and public health are grouped in public health, an area that emerges in the 1970s in this field, two aspects should be highlighted: the notion of collective remains modern and disciplinary traits with changes and redesigns that they favor diversity assembly and involve a polycentric; all are replaced by multiplicity as a new term that recasts and preserves combined units. We emphasize the modern health care speech inhabiting the bodies, pathologizing mills linked to social formatting and policy on the medicalization of life, determining the normalization of individuals and establishing the control of society as a predominant way of life. The Public Health points out the quickest ways of outdoor control to replace the old disciplines operating in the time of a closed system - hospitals, allowing broaden the horizons of analysis and intervention on reality. But resist we must. Under the aegis of the philosophy of difference, we dare think health care in their disruptive character, acting in the reversal of power over life in power life. The becoming-care breaks out of constitutive processes of living and the availability of production, tensing and destabilizing the majoritarian model of health care, creating worlds, touting modes of expression and connectivity of life in its multiple trials.